Weakly-Activated Phenol Derivatives as New Green Electrophilic Partners in Suzuki–Miyaura and Related C-C Couplings - Jules Perney; Alexandre Humblot-Negri; Carlos Vaca-Garcia; Sébastien Lemouzy; Martine Urrutigoïty (Molecules)
In recent years, there has been growing interest in the development of greener alternatives to traditional reagents used in carbon–carbon coupling reactions, particularly in response to environmental concerns. The commonly used aryl halides, despite being highly reactive in the Suzuki–Miyaura coupling (SMC), pose significant environmental risks. As a result, research has shifted towards exploring the use of phenols, which are widely accessible and environmentally benign. However, phenols are considerably less reactive due to the poor leaving group properties of the hydroxyl group, necessitating prior activation to facilitate their use in coupling reactions. This work aims to review the recent investigations on the activation strategies for phenols, focusing on their application in the Suzuki–Miyaura and related C-C couplings. In addition, the exploration of the potential of conducting the activation step “in situ” will also be discussed. We hope that this article will pave the way for the development of more sustainable and efficient coupling methodologies, addressing both ecological and practical challenges in organic synthesis.